PEMBELAJARAN BAHASA ARAB BERBASIS KARAKTER DI SEKOLAH DASAR - Dudung Hamdun (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2016)
Nowadays, Indonesia still faces various problems related to the moral issues. Many cases occur in the society which should be solved by the educators, such as: corruption, collusion, and nepotism in all level of Indonesian governmental institutions, juvenile delinquency, and drugs. To prevent those, the Indonesian government through education minister in 2010 established the 18 values of characters building. At school, this character building becomes the pivotal role in developing the characters of the students. This paper tries to describe how the teaching of Arabic done by implementing the values of the character building. The character building at SD Muhammadiyah Kleco is done by centralizing the role of teachers. The role of teachers in building the moral characters of the students is done by applying the principle role as teacher, such as: catalyst, row model, inspirer, motivator, dynamist, and evaluator. The teaching of Arabic skills,-listening (istima'), speaking (kalam), reading (qiro'ah), and writing (kitabah)-, is done by implementing the moral character such as: religiosity, honesty, tolerance, independency, democratic, curiosity, friendship, social awareness, responsibility, discipline, environmental care, and appreciation.